PRELIMINARY STUDIES ON THE USE OF THE DIAGRAM RANK OF THE ORAL HEALTH OF THE BABY IN AN INTERDISCIPLINARY HEALTH PROGRAM - Silva, Rosilene Teles; Vilela, Joana Estela Rezende; Rank, Rise Iuata; Gama, Karla Regina; Rank, Marcos Sampaio; Ogawa, Wataro Nelson (REVISTA CEREUS, 2018)
Considering the difficulty of recording intraoral data of edentulous children in dentistry, the Rank Diagram of the oral health of the baby was created and designed to meet this need. The present study aimed to verify registrations performed from 2012 to 2015, and also to understand the degree of examiner satisfaction. The research was carried out in two stages: 1) a cohort study with 138 charts completed during the intraoral examinations of children 0-36 months of age (2012-2015); 2) the degree of satisfaction of the Diagram was verified by 33 examiners submitted to 6 months of filling out in 2016. The most frequent changes in the soft tissues were ankyloglossia (10.9%) and inclusion cysts (8.7%); as for the hard tissues, it was caries (8.6%) and enamel fracture (5.0%). The examiners verified the Rank Diagram as satisfactory (89%), but the chi-square test showed significance in the dissatisfaction of the recording site of the observations in the Diagram (p <0.0001 and χ2 = 59). The Rank Diagram allowed for the registration of the intraoral changes from the birth of the child until 3 years of age. The datasheet adapted to the quarterly program was preliminarily well evaluated in several aspects, but requires some adjustments to improve the recording space of the intraoral observations.